2014
DOI: 10.1111/1751-2980.12186
|View full text |Cite
|
Sign up to set email alerts
|

New dual therapy for primary treatment of Helicobacter pylori infection: A prospective randomized study in Shanghai, China

Abstract: The modified dual therapy with high doses of rabeprazole and amoxicillin is considered an effective and safe primary therapy for H. pylori eradication and could be recommended as the first-line eradication regimen for certain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Furuta et al have long emphasised that in order to reliable achieve cure rates over 90%, it is important to administer amoxicillin approximately every 6 h and maintain the pH at 6 or above 80 110. Although several studies have suggested that dosing of amoxicillin such as every 8 h may also be effective,81 111 these studies have been done in Asia where atrophic gastritis and slow CYP2C19 metaboliser’s are common.…”
Section: Improving the Results With Bismuth By Increasing The Effect mentioning
confidence: 99%
“…Furuta et al have long emphasised that in order to reliable achieve cure rates over 90%, it is important to administer amoxicillin approximately every 6 h and maintain the pH at 6 or above 80 110. Although several studies have suggested that dosing of amoxicillin such as every 8 h may also be effective,81 111 these studies have been done in Asia where atrophic gastritis and slow CYP2C19 metaboliser’s are common.…”
Section: Improving the Results With Bismuth By Increasing The Effect mentioning
confidence: 99%
“…Studies have been done in many countries including Korea, Japan, and the United States, and most report cure rates below 90% . Studies in China have also reported variable cure rates …”
Section: Discussionmentioning
confidence: 99%
“…13,[18][19][20][21] Studies in China have also reported variable cure rates. 6,7,22 Amoxicillin, a β-lactam antibiotic, is currently widely used in the treatment of H. pylori infections. It is well tolerated, and primary resistance among H. pylori is rare and was not found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Japan, using 10 mg rabeprazole and 500 mg amoxicillin, 4 times a day for 2 weeks, reported a cure rate of 90.9% (95% CI: 81.2–96.6) in the ITT analysis and 93.8% (95% CI: 84.8–98.3) in the PP analysis [ 43 ]. In addition, a study in China reported that eradication was achieved in 89.8% (95% CI: 82.1–87.6) of 117 subjects in the ITT analysis and 93.0% (95% CI: 86.4–99.6) in the PP analysis, using 20 mg rabeprazole twice and 1 g amoxicillin 4 times a day, for 2 weeks [ 44 ]. In this study, the eradication rate was 79.3% (23/29) in the ITT analysis and 82.1% (23/28) in the PP analysis.…”
Section: Discussionmentioning
confidence: 99%